Duration of anticoagulation after isolated pulmonary embolism. Issue 5 (25th February 2016) - Palareti, Gualtiero; Cosmi, Benilde; Antonucci, Emilia; Legnani, Cristina; Erba, Nicoletta; Ghirarduzzi, Angelo; Poli, Daniela; Testa, Sophie; Tosetto, Alberto; Pengo, Vittorio; Prandoni, Paolo
In the D-dimer and ULtrasonography in Combination Italian Study (DULCIS), serial D-dimer measurement in combination with assessment of residual thrombosis (in patients with deep vein thrombosis (DVT)) identified patients who safely discontinued anticoagulation after an unprovoked venous thromboembolism (VTE). In this subgroup analysis, the value of D-dimer tests was assessed in patients with isolated pulmonary embolism (PE) compared with those with DVT, with or without PE (DVT/PE). The DULCIS database was reanalysed in relation to this target. 26.8% of the DULCIS patients had isolated PE as the index event; this was more prevalent in females (34.1%) than in males (21.1%; p<0.0001). The rate of positive D-dimer was similar in isolated PE and DVT/PE. The rate of recurrences was not different in isolated PE or DVT/PE patients (4.8% ppy versus 3.8% ppy; nonsignificant) who stopped anticoagulation for negative D-dimer, but it was markedly high (11.2% ppy; p<0.0001) in those with isolated PE who remained without anticoagulation despite positive D-dimer. Recurrences were more frequently new isolated PE in patients with isolated PE than with DVT/PE (six (46.2%) out of 13 versus two (7.4%) out of 27; p=0.0085). Serial D-dimer assessment can inform on the risk of recurrent VTE and help determine the duration of anticoagulation in patients with isolated PE. Serial D-dimer assessment can inform on the risk of recurrent thromboembolism after an isolated pulmonary embolism http://ow.ly/X3OwL